Using Drosophila to study mechanisms of hereditary hearing loss - Tongchao Li; Hugo J. Bellen; Andrew K. Groves (The Company of Biologists, 2018)
Johnston's organ - the hearing organ of Drosophila - has a very different structure and morphology to that of the hearing organs of vertebrates. Nevertheless, it is becoming clear that vertebrate and invertebrate auditory organs share many physiological, molecular and genetic similarities. Here, we compare the molecular and cellular features of hearing organs in Drosophila with those of vertebrates, and discuss recent evidence concerning the functional conservation of Usher proteins between flies and mammals. Mutations in Usher genes cause Usher syndrome, the leading cause of human deafness and blindness. In Drosophila, some Usher syndrome proteins appear to physically interact in protein complexes that are similar to those described in mammals. This functional conservation highlights a rational role for Drosophila as a model for studying hearing, and for investigating the evolution of auditory organs, with the aim of advancing our understanding of the genes that regulate human hearing and the pathogenic mechanisms that lead to deafness.